Trains Run! - Lyon, George Ella 1949-; Lyon, Benn; Wiggins, Mick (New York : Atheneum Books for Young Readers, 2019)
Illustrations and simple, rhyming text reveal different kinds of trains, how they run, and the sounds they make.
Keywords: Railroad trains -- Juvenile fiction; Railroad travel -- Juvenile fiction; Railroad trains -- Fiction; Railroad travel -- Fiction; Stories in rhyme; Picture books; Stories in rhyme